2020
DOI: 10.1155/2020/3549704
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Ameliorates Mitochondria-Dependent Neuronal Apoptosis after Spinal Cord Ischemia-Reperfusion Injury Partially through Inhibiting Oxidative Stress and Promoting Mitophagy

Abstract: Ischemia-reperfusion injury is the second most common injury of the spinal cord and has the risk of neurological dysfunction and paralysis, which can seriously affect patient quality of life. Salidroside (Sal) is an active ingredient extracted from Herba Cistanche with a variety of biological attributes such as antioxidant, antiapoptotic, and neuroprotective activities. Moreover, Sal has shown a protective effect in ischemia-reperfusion injury of the liver, heart, and brain, but its effect in ischemia-reperfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 80 publications
2
48
1
Order By: Relevance
“…Cellular stresses, including hypoxia, ischemia, and glucose deprivation, can cause damage or dysfunction of mitochondria 7 . In addition, researches showed that mitophagy exerts a protective function in the liver 8 . Mitophagy, a complex process that rapidly and selectively removes long-lived or damaged mitochondria in an autophagy-dependent manner, is an adaptive response of mitochondria to various stress damages, which was previously identified to play an important role in IRI 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Cellular stresses, including hypoxia, ischemia, and glucose deprivation, can cause damage or dysfunction of mitochondria 7 . In addition, researches showed that mitophagy exerts a protective function in the liver 8 . Mitophagy, a complex process that rapidly and selectively removes long-lived or damaged mitochondria in an autophagy-dependent manner, is an adaptive response of mitochondria to various stress damages, which was previously identified to play an important role in IRI 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, excessive ROS induce cardiomyocyte apoptosis and then lead to abnormal cardiomyocyte death, which may be one of the important reasons why cardiac hypertrophy progresses to heart failure [ 2 ]. Although salidroside exhibits the protective effect against oxidative stress [ 18 , 19 ], the mechanisms remain unclear. In this research, H9C2 cells derived from embryonic rat heart tissue were exposed to H 2 O 2 in vitro to establish a cell injury model.…”
Section: Introductionmentioning
confidence: 99%
“…Without affecting ER stress, curcumin protects mitochondria from oxidative damage by attenuating the apoptosis of cortical neurons (Zhu et al, 2004 ). In primary cultured spinal neurons, salidroside (Sal) treatment decreases apoptosis by activating PINK-Parkin pathways, leading to mitophagy of mitochondria (Gu et al, 2020 ). Similar to its effects on AD, Aβ 1–42 induces neuronal apoptosis by concurrently upregulating mitochondrial fission protein dynamin-related protein 1 (Drp1) and downregulating mitofusin 1/2 (Mfn1/2) and dynamin-like GTPase (OPA-1) in primary cultures of mouse cerebral cortical neurons (Han et al, 2017 ).…”
Section: Ca 2+ Signaling Impairs Neuronal Functionmentioning
confidence: 99%